(untitled) (Discourse of Law and Administration, 2025)
The scientific work presents, above all, the history of initiatives preceding the polish electronic platform of public administration services (ePUAP) and problems related to the implementation of the portal itself and its second version (ePUAP2). Author describes position of the electronic platform for public administration services (ePUAP) in the Polish legal system. The article presents, among others, statistical data showing the development of the platform and its strengths and weaknesses. The last part of the scientific work also presents the functioning of platforms with similar applications in other legal systems and the further expected fate of ePUAP in Poland.